Simulation and Fabrication of Double Barrier Structure of P-I-N Amorphous Silicon (a-Si) Device - Ida Hamidah; Kardiawarman Kardiawarman; Budi Mulyanti; Andi Suhandi (Journal of Mathematical and Fundamental Sciences, 2001)
Abstract. The application of double barrier (DB) structure in p-i-n amorphous silicon (a-Si) device was studied. The theoretical study was done to obtain device parameters such as tunneling probability and current density. The tunneling probability was calculated by employing the Schroedinger equation, WKB approximation and Green function. Width of potential well, width and height of barrier were varied to obtain the highest tunneling probability value. The current density was contributed by diffusion, and tunneling current densities. It was found that current density had a peak of 3950 A/m2 at 0.56 volt forward bias. Furthermore, the fabrication of p-i-n a-Si device with double barrier structure was successfully carried out. To realize the double barrier structure, optimization of optical band gap of barrier a-SiC:H was done by varying ratio of CH4 to [CH4+SiH4]. The fabrication of p-i-n a-Si device was then done by using Plasma Enhanced Chemical Vapor Deposition (PECVD) technique with a structure of glass substrate/TCO/p-a-Si:H (2.15 eV;140Ã…)/i-a-Si:H (1.81 eV;1800 Ã…)/barrier a-SiC:H (2.36 eV;45 Ã…)/potential well i-a-Si:H (1/81 eV; 30 Ã…)/barrier a-SiC:H (2.36 eV; 45 Ã…)/n-a-Si:H (1.81 eV;180 Ã…)/Al. The I-V characteristic of the device showed a peak current calue at 0.55 forward bias. Simulasi dan Fabrikasi Struktur Double Barrier pada Divais Amorphous SiliconSari. Aplikasi struktur double barrier (DB) pada divais amorphous silicon (a-Si) telah dilakukan untuk memperoleh beberapa parameter divais seperti probabilitas tunneling dan rapat arus. Probabilitas tunneling dihitung dengan menerapkan persamaan Schroedinger, pendekatan WKB dan fungsi Green. Lebar sumur potensial, lebar dan tinggi barrier telah divariasikan untuk memperoleh harga probabilitas tunneling yang maksimum. Rapat arus total dari divais dalam perhitungan ini merupakan jumlah dari rapat arus difusi dan rapat arus tunneling. Diperoleh bahwa rapat arus total memiliki nilai maksimum sebesar 3950 A/m2 pada tegangan bias maju 0,56 volt. Selanjutnya, telah berhasil juga difabrikasi divais p-i-n a-Si dengan struktur double barrier. Didapatkan bahwa karakteristik I-V dari divais menunjukkan adanya puncak rapat arus pada tegangan bias maju 0,55 volt.ihamidah@eudoramail.com